We wanted you - Rosenberg, Liz.; Catalanotto, Peter (Brookfield, Conn. : Roaring Brook Press, 2002)
Parents tell how they waited and prepared for the child that they wanted so much.
Keywords: Parent and child -- Fiction; Adoption -- Fiction